Activation of midbrain and ventral striatal regions implicates salience processing during a modified beads task. - Christine Esslinger (Public Library of Science (PLoS), 2013)
Introduction Metacognition, i.e. critically reflecting on and monitoring one's own reasoning, has been linked behaviorally to the emergence of delusions and is a focus of cognitive therapy in patients with schizophrenia. However, little is known about the neural processing underlying metacognitive function. To address this issue, we studied brain activity during a modified beads task which has been used to measure a "Jumping to Conclusions" (JTC) bias in schizophrenia patients. Methods We used functional magnetic resonance imaging to identify neural systems active in twenty-five healthy subjects when solving a modified version of the "beads task", which requires a probabilistic decision after a variable amount of data has been requested by the participants. We assessed brain activation over the duration of a trial and at the time point of decision making. Results Analysis of activation during the whole process of probabilistic reasoning showed an extended network including the prefronto-parietal executive functioning network as well as medial parieto-occipital regions. During the decision process alone, activity in midbrain and ventral striatum was detected, as well as in thalamus, medial occipital cortex and anterior insula. Conclusions Our data show that probabilistic reasoning shares neural substrates with executive functions. In addition, our finding that brain regions commonly associated with salience processing are active during probabilistic reasoning identifies a candidate mechanism that could underlie the behavioral link between dopamine-dependent aberrant salience and JTC in schizophrenia. Further studies with delusional schizophrenia patients will have to be performed to substantiate this link.